2021
DOI: 10.24127/pj.v10i1.3348
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Vocabulary Mastery and Fluency in Speaking at Universitas Tanjungpura

Abstract: This research, entitled “Correlation Between Vocabulary Mastery and Fluency in Speaking” was carried out to the fifth semester students of English Education Study Program. The population of this research is fifth semester students of English Education Study Program of Teacher Training and Education Faculty at Tanjungpura University with the sample size of 30. The result of data analysis revealed the correlational between both variable from the samples is showing the correlational coefficient (r) value of 0.19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(14 reference statements)
0
8
0
2
Order By: Relevance
“…Another researcher Aidil Syah Putra (2017), had a similar result; his research showed an improvement in the students' speaking ability through motivation. It can be seen in the students' speaking scores which had reached the score of Minimum Mastery Criterion (KKM).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another researcher Aidil Syah Putra (2017), had a similar result; his research showed an improvement in the students' speaking ability through motivation. It can be seen in the students' speaking scores which had reached the score of Minimum Mastery Criterion (KKM).…”
Section: Introductionmentioning
confidence: 73%
“…The study results by Aidil Syah Putra (2017) indicate an increase in students' speaking ability through motivation. The results of this study indicate that students' speaking ability increases due to increased motivation.…”
Section: Introductionmentioning
confidence: 82%
“…Following the data collection, the researcher assessed the speaking performances based on the rubric score suggested by Brown, Harris, and Harmer (Putra, 2017). To ensure reliability and minimize bias in the assessment process, two assessors were involved: the researcher and an English lecturer at STKIP Abdi Pendidikan Payakumbuh, who taught speaking courses and served as the research thesis advisor, Hervina, M.Pd.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa persepsi mahasiswa PGSD terhadap mata pelajaran bahasa Inggris bagi siswa sekolah dasar di era globalisasi berada dalam kategori tinggi dengan rata-rata persentase 80%. Artinya, pembelajaran mata pelajaran bahasa Inggris di sekolah dasar sangat penting dilaksanakan terutama di era globalisasi karena pada usia tersebut anak masih mudah mempelajari dan tertarik dengan hal yang baru dan dapat membantu anak untuk lebih mudah memahami dan mempelajari bahasa Inggris di tingkat selanjutnya yang faktanya banyak siswa SMP belum memahami konsep bahasa Inggris dengan baik [11,12].…”
Section: Hasil Dan Pembahasanunclassified